A Gun Took My Child - Edmonds, Regina (Journal of the Motherhood Initiative for Research and Community Involvement, 2019)
The death of a child to gun violence is a particularly devastating loss. The reactions of mothers to this loss, described here, indicate how their experience engenders extreme distress and produces symptoms of psychological trauma. The impact of child loss is intensified for mothers due to the guilt that many feel for having failed to protect their child. Ways of healing from this trauma and the usefulness of mother-centred approaches to recovery are described, and they demonstrate that matricentric feminism is especially valuable in helping mothers move forward in their lives. Although these healing practices do not cite matricentric feminism as their source, it is clear from the descriptions of healing presented by the mothers here that they use matrifocal narratives for healing purposes; they use them as a space to speak about not only the loss of their child but also the loss of identity as competent mothers as well as their despair over never seeing their child move into the future. Matricentric feminism, therefore, can contribute a great deal to understanding and supporting mothers as they struggle to heal.